2019
DOI: 10.1111/jfbc.12817
|View full text |Cite
|
Sign up to set email alerts
|

Binding of aromatic compounds with soy protein isolate in an aqueous model: Effect of pH

Abstract: Interactions of the flavoring compounds hexyl acetate (HxAc), heptyl acetate (HpAc), linalyl formate (LiFo), linalyl acetate (LiAc), geraniol, linalool, limonene, and myrcene with soy protein isolate (SPI) were estimated in pH 3.0, 6.0, and 9.0 aqueous solutions using headspace solid‐phase microextraction gas chromatography–mass spectrometry (SPME–GC–MS). The binding capacity of HxAc, HpAc, LiFo, LiAc, geraniol, and linalool increased in the pH of the medium from 3 to 9. For limonene and myrcene, an unexpected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 50 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…Knowledge of these types of interactions is often useful when designing plant‐based food products. For instance, plant‐based proteins may bind to aromatic flavor molecules in beverages, thereby altering the overall flavor profile (Guo, He, Wu, Zeng, & Chen, 2019; Wang & Arntfield, 2015). In some cases, this would be desirable because it reduces the level of off‐flavors, but in other cases it may be undesirable because it alters the anticipated flavor profile.…”
Section: Ingredient Functionalitymentioning
confidence: 99%
“…Knowledge of these types of interactions is often useful when designing plant‐based food products. For instance, plant‐based proteins may bind to aromatic flavor molecules in beverages, thereby altering the overall flavor profile (Guo, He, Wu, Zeng, & Chen, 2019; Wang & Arntfield, 2015). In some cases, this would be desirable because it reduces the level of off‐flavors, but in other cases it may be undesirable because it alters the anticipated flavor profile.…”
Section: Ingredient Functionalitymentioning
confidence: 99%
“…1e–h). SPI also shows the presence of a hydrophobic surface (Viry et al ., 2018), which may serve as the second binding site for ethyl caprylate and undecanal at high concentrations (Guo et al ., 2019a, 2019b). Feyzi and others had been reported that safranal binding to whey possesses the similar results (Feyzi et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…(2017) have reported that the ‘salting‐out’ effect of limonene is observed in the case of mixed esters and limonene in aqueous SPI. Using SPME‐GC/MS, the ‘salting‐out’ effects of limonene were also found to be exhibited in aqueous SPI (Guo et al ., 2019a, 2019b). However, based on dynamic coupled column liquid chromatography method, which provides a direct measure of interactions in the liquid through the intermediary phases of total solubility, some studies have reported that limonene has a strong interaction with β‐lactoglobulin (Jouenne & Crouzet, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…By an 8-anilinonaphthalene-1-sulfonic acid (ANS) fluorescent probe method, in the aqueous solution, SPI hydrophobicity was determined with modifications (21). SPI was centrifuged at 12,000 × g, times is 15 min, temperature is 37 • C, the supernatants were diluted in 20 mmol/L citric acid phosphate buffer (pH 5.0-pH9.0), obtain SPI concentrations ranging from 0.1 to 0.002 mg/mL.…”
Section: Determination Of Surface Hydrophobicity Of Soybean Protein I...mentioning
confidence: 99%